2017
DOI: 10.1021/acs.chemrev.7b00094
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biomimetic Materials for Engineering of the Three-Dimensional Cell Microenvironment

Abstract: The cell microenvironment has emerged as a key determinant of cell behavior and function in development, physiology, and pathophysiology. The extracellular matrix (ECM) within the cell microenvironment serves not only as a structural foundation for cells but also as a source of three-dimensional (3D) biochemical and biophysical cues that trigger and regulate cell behaviors. Increasing evidence suggests that the 3D character of the microenvironment is required for development of many critical cell responses obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
499
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 644 publications
(504 citation statements)
references
References 1,341 publications
(2,349 reference statements)
4
499
0
1
Order By: Relevance
“…[10] Previous studies have reported the adhesion ligand modified microparticles for cell adsorptions and proliferations, which combined the advantages of both 2D adherent cultures and 3D suspension cultures. Considering the challenging survival rates of the implanted stem cells, it was rather vital to expand the stem cells while maintaining the self-proliferation and multipotency.…”
Section: Polyhipe-based Ecmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Previous studies have reported the adhesion ligand modified microparticles for cell adsorptions and proliferations, which combined the advantages of both 2D adherent cultures and 3D suspension cultures. Considering the challenging survival rates of the implanted stem cells, it was rather vital to expand the stem cells while maintaining the self-proliferation and multipotency.…”
Section: Polyhipe-based Ecmsmentioning
confidence: 99%
“…[2] Furthermore, the tunable nanostructures and the distinct properties (e.g., acoustic sensitivity and photomanipulation activity) have paved the ways for high-throughput multiplex assay, noninvasive diagnosis, stimuli-responsive therapy, and tissue regeneration. [10] Through the integration of "yin" and "yang," emulsion particulate technique may shed light on the development of novel hollow structures for improved biomedical applications. [10] Through the integration of "yin" and "yang," emulsion particulate technique may shed light on the development of novel hollow structures for improved biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The new vascular network not only supplies the oxygen and nutrients essential for tumor survival but also provides a route for tumor cell intravasation and extravasation, supporting the tumor development and key events of the metastatic cascade and drug resistance. [9,26,27] The protein portion of the ECM mainly includes collagen, elastin, laminin, and fibronectin, being its spatial distribution dependent of tissue type. [9,26,27] The protein portion of the ECM mainly includes collagen, elastin, laminin, and fibronectin, being its spatial distribution dependent of tissue type.…”
Section: Role Of Microenvironment In Tumor Pathophysiology and Therapmentioning
confidence: 99%
“…[29] This protein network integrates negatively charged polysaccharides produced by the cells which fill the interstitial space by the formation of glycosaminoglycans (GAGs) and proteoglycans, contributing to the compressive resistance of the tissues. [9] Native tissues show mechanical properties that vary from effective elastic moduli of 0.1 kPa in "soft" neural tissues to effective elastic moduli of 20 million times higher in stiff ("hard") bony tissues. The dynamic interaction and structural arrangement of the ECM is closely related with the mechanical stiffness of the tissue and, in turn, with its biological function.…”
Section: Role Of Microenvironment In Tumor Pathophysiology and Therapmentioning
confidence: 99%
See 1 more Smart Citation